(3YLGFH GdHdOGfs - (3RcQjG Hf eMeO Hf eMehO,GdnbrRphjfj, CHh jMji YeGO GdOjf,J (B682 (3g` s
(3ChdgG (B:s
(3GdYR dc hGdLdGd dcHQjGFc Efi bO LeYJ ai gPG GdcJGH eG hbY di hYQaJg hSeYJ Hg hTGgOJg ef dWGFa UfY Gddg JYGdi hYLGFH MceJg s
(3BNQgG (B:s
(3hMci Cf ai HYV GdSfjf NQL Ydjge gPg GdSecI aGLJeY Gdbhe YdjgG hfbHhG CPfgG GfJgi Yde Cgd HdGOfG , hGddg CYde HeG hQGA Pdc ef GdHdGO hGdJLGQ , hdjcf gPG BNQ GdcdGe hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedc HGSe eMeO Hf CMeO GdZjWi GdTGaYis
(3cJH Ydi GdUaMI GdCNjQI Cfg HdZ ebGHdI Ydi jO eGdcg YHO GdQMef Hf YeQ GdbWHi SfI EMOi hJSYeGFI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1126s
Keywords: (3GdLZQGajG h GdHdOGfs